Efforts to Improve Students' Problem Solving Abilities and Mathematical Disposition by Implementing the Problem Based Learning Model Assisted by PowerPoint-Based Interactive Learning Media - Hikmah, Nurul; Isnawati Lujeng Lestari (Noumerico: Journal of Technology in Mathematics Education, 2025)
This research aims to determine the difference in improving problem-solving abilities and mathematical disposition of students who use the Problem Based Learning model assisted by PowerPoint-based interactive learning media and students who are given the application of conventional learning. The research method used is quantitative research in the form of a quasi-experiment. The data collection technique used in this research is using pretest and post test. Data analysis was carried out using parametric tests in the form of t-tests. The results of data analysis show that students’ problem-solving abilities who use Problem Based Learning experience compared to students who take part in conventional learning is 62,55% to 43,5%. Apart from that, the increase in students' mathematical disposition for students who used the Problem Based Learning model compared with students who took part in conventional learning is 73,90% to 68,93%. This means that it can be concluded that there is a difference in the increase in problem-solving abilities and mathematical disposition of students who use the Problem Based Learning model assisted by PowerPoint-based interactive learning media and students who are given the application of conventional learning